PWE-365 Exploring adr performance in the nhs bowel scope programme. (22nd June 2015) - Bevan, R; Blanks, R; Nickerson, C; Patnick, J; Loke, R; Saunders, B; Stebbing, J; Tighe, R; Veitch, A; Rees, CJ
Abstract : Introduction: A new arm of the NHS Bowel Cancer Screening Programme began in 2013. One-off flexible sigmoidoscopy (FS) is to be offered to all 55 year olds. Six pilot sites were chosen to start this screening programme, with roll out to the rest of the country planned by 2016. A benchmark adenoma detection rate (ADR) for endoscopists within the programme is being discussed. Method: The NHS Bowel Cancer Screening System database was interrogated for all FS performed at the pilot sites May '13-May '14. Data were extracted at procedural level. Participants aged 55 were included in analyses. Overall ADR was calculated. Data of endoscopists with ≥30 procedures were reviewed. Funnel plots were produced for ADR, and gender adjusted observed:expected adenoma detection ratio (GAADR). GAADR was calculated using the population risk of adenoma detection within the programme by gender, predicting how many adenomas each endoscopist should find based on case mix, and calculating the ratio of predicted:observed adenomas detected. Mean negative withdrawal time (time taken to withdraw scope when no adenoma/cancer detected) for each endoscopist was calculated and considered in 3 groups – those with GAADR <0.85, 0.85 to <1.1, and ≥1.1. Results: 8582 subjects underwent FS, of which 8494 (99.0%) were aged 55. 4420 (52%) male, 4074 (48%) female. Adenomas were detected in 507 males (11.5%) vs 273 females (6.7%, p < 0.001). 44 endoscopists performed ≥30 FS. These endoscopists performed 8256 FS (range 32–476). Overall programme ADR was 780/8494 (9.2%). GAADR mean 0.99 (range 0.00–2.05). Funnel plots were produced; Figure 1(a) shows ADR and Figure 1(b) shows GAADR by endoscopist, with control lines at 95% and 99.8%. Increased mean negative withdrawal time (WT) is associated with higher GAADR (2.63min when GAADR <0.85, 3.02 min when 0.85 to <1.1, and 3.25 min when ≥1.1). Conclusion: These data show that for 55 year olds within the BowelScope programme, overall ADR is 9.2%. ADR between endoscopists varies, and reasons for these variations should be investigated and acted upon. There is a significant difference between adenoma detection in men and women, and as such, a gender adjusted ratio could be used when analysing individual endoscopists' performance should their ADR fall below a defined benchmark. The funnel plots demonstrate most endoscopists performing within an acceptable range, and highlights those that may need further investigation. A similiar approach could be taken with regards to withdrawal times, and depth of insertion to establish the effect of these on ADR. Disclosure of interest: None Declared.